Neural Predictors of Giving in to Temptation in Daily Life - Lopez, Richard B.; Hofmann, Wilhelm; Wagner, Dylan D.; Kelley, William M.; Heatherton, Todd F. (Psychological Science, 2014)
The ability to control desires, whether for food, sex, or drugs, enables people to function successfully within society. Yet, in tempting situations, strong impulses often result in self-control failure. Although many triggers of self-control failure have been identified, the question remains as to why some individuals are more likely than others to give in to temptation. In this study, we combined functional neuroimaging and experience sampling to determine if there are brain markers that predict whether people act on their food desires in daily life. We examined food-cue-related activity in the nucleus accumbens (NAcc), as well as activity associated with response inhibition in the inferior frontal gyrus (IFG). Greater NAcc activity was associated with greater likelihood of self-control failures, whereas IFG activity supported successful resistance to temptations. These findings demonstrate an important role for the neural mechanisms underlying desire and self-control in people’s real-world experiences of temptations.